Evaluation of the Hydraulic Fracturing Implementation at Well WEA-01 Layer A3 - Kaesti, Edgie Yuda; Suwardi, Suwardi; Widyaningsih, Ratna; Yusrizal, Muhammad Zakiy; Rifqi, Wijaya Ananditya; Hartoyo, Puji (Journal of Petroleum and Geothermal Technology, 2023)
The WEA-01 well produces in the A3 productive layer, talangakar formation with a layer thickness of 32.80 ft with a perforation interval of 4340.55 – 4360.24 ftMD where from petrophysical data this formation is dominated by sandstone with a permeability of 3 mD which is classified as low and a tight formation (Koesoemadinata, 1980) with 10% porosity. This is the basis for the stimulation of Hydraulic Fracturing. Hydraulic fracturing that has been implemented needs to be evaluated to find out whether the implementation has been carried out optimally or not.The method to be used in the evaluation of the WEA-01 Well hydraulic fracturing implementation includes data collection, then manual calculations and evaluation with actual data. The first evaluation was to calculate the geometry of the fracture using the 2D PKN method, the second evaluation was to calculate the price increase in the productivity index using the Cinco-ley Samaniego and Dominique method and the third evaluation was to analyze the IPR curve (Inflow Performance Relationship) before fracturing using the Darcy method and after fracturing using the Pudjo Sukarno method.Based on the results of manual fracture geometry calculations using the 2D PKN method, the results obtained are fracture length (Xf) of 200.07 ft, fracture height (hf) of 32.80 ft, and fracture width (wf) of 0.23 inch, fracture conductivity of 5094.70 mD-ft, and FCD 8.5, while the results of calculating the average permeability of formations using the Howard & Fast method obtained permeability after Hydraulic Fracturing of 15.71 mD or an increase of 5.2 times from the initial conditions and calculating the productivity index using the Cinco-Ley, Samaniego & Dominique method obtained an increase in PI prices of 3.45 times and from the determination of the IPR curve, the results obtained from the comparison of the IPR curve showed an increase in the production rate from 45.00 BOPD to 330 BOPD. Based on the increase in the fluid production rate, the implementation of Hydraulic Fracturing that has been carried out can be said to be successful.Keywords – hydraulic fracturing, fracturing fluid, proppant, fracture geometry, permeability, conductivity